PENGARUH INOVASI TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR INDUSTRI ENERGI DI INDONESIA - Wenny Chandra; Sumani Sumani (Jurnal Akuntansi, 2023)
Sustainability is an important issue that continues to be intensified through various activities such as CSR and green investment. This study aims to examine, review, and explain the effect of innovation on the profitability of energy industry companies through the mediation of CSR and green investment activities. The data used in this study are secondary data obtained from the Indonesia Stock Exchange (IDX). The population in this study were 76 energy industry companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period. Of this population, 24 energy industry companies met the research criteria. Data processing was carried out through SmartPLS software version 3.2.9. Testing is done through the inner model test which aims to test the relationship between exogenous variables and endogenous variables using the coefficient of determination (R2), predictive relevance (Q2), effect size (F2), and hypothesis testing (t-stat and p-value). The results showed that there was no significant effect of innovation on CSR, green investment, and profitability as dependent variables. In addition, there is no significant effect of CSR and green investment as independent variables on profitability. Finally, there is no significant effect of innovation on profitability through the mediation of CSR and green investment.